Effectiveness of Low-Cost Ozone Treatment in Preserving the Postharvest Quality of Chilli Pepper under Tropical Ambient Storage - Indriati Meilina Sari; Kiky Nurfitri Sari; Andika Prawanto; Paisal Ansiska (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Postharvest losses of red chilli peppers remain a significant challenge in tropical regions, particularly under ambient storage conditions where access to refrigeration is limited. This study evaluates the effectiveness of simple ozonation at different exposure durations in maintaining the quality of red chilli peppers and identifies the optimal treatment duration based on quality preservation performance. A controlled experimental design with four treatments, consisting of no ozone exposure and ozonation for 5, 10, and 15 min, was applied. Quality parameters included weight retention, firmness, vitamin C content, water content, and microbial load were observed during ten days of storage. The results showed that ozonation significantly affected all measured parameters, with longer exposure durations generally improving quality retention and reducing microbial growth. However, the 10-min treatment demonstrated comparable performance to that of 15-min treatment across most variables, indicating that an optimal exposure duration had been reached. These findings suggest that simple ozonation can serve as a practical and effective postharvest approach for maintaining red chilli quality under tropical ambient conditions, particularly for small-scale applications.